2018
DOI: 10.1007/s40119-018-0121-2
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Coated Balloon-Only Percutaneous Coronary Intervention for the Treatment of De Novo Coronary Artery Disease: A Systematic Review

Abstract: Percutaneous coronary intervention (PCI) with a drug coated balloon (DCB) is a novel treatment which seeks to acutely dilate a coronary stenosis and deliver an anti-proliferative drug to the vessel wall (reducing the risk of re-stenosis), without implanting a drug eluting stent (DES). In this study, we performed a systematic review of stentless DCB-only angioplasty in de novo coronary artery disease. We identified 41 studies examining the effects of DCB-only PCI in a variety of clinical scenarios including sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 64 publications
0
20
0
1
Order By: Relevance
“…Drug-coated balloon therapy (otherwise known as drug-eluting balloon, DEB) has been proposed as an alternative to DES in SVD, obviating the need for implantation of a foreign body into a small artery [57]. The technique is based on rapid delivery of an antiproliferative drug to the arterial wall from a semi-compliant balloon covered with a lipophilic matrix [58]. Therapeutic agents, most commonly paclitaxel, are delivered during single balloon inflation, which should last between 30 and 60 seconds depending on the DCB type [58].…”
Section: Drug-coated Balloonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drug-coated balloon therapy (otherwise known as drug-eluting balloon, DEB) has been proposed as an alternative to DES in SVD, obviating the need for implantation of a foreign body into a small artery [57]. The technique is based on rapid delivery of an antiproliferative drug to the arterial wall from a semi-compliant balloon covered with a lipophilic matrix [58]. Therapeutic agents, most commonly paclitaxel, are delivered during single balloon inflation, which should last between 30 and 60 seconds depending on the DCB type [58].…”
Section: Drug-coated Balloonsmentioning
confidence: 99%
“…The technique is based on rapid delivery of an antiproliferative drug to the arterial wall from a semi-compliant balloon covered with a lipophilic matrix [58]. Therapeutic agents, most commonly paclitaxel, are delivered during single balloon inflation, which should last between 30 and 60 seconds depending on the DCB type [58]. A crucial step prior to deployment of DCB consists of adequate lesion preparation with a successful predilatation to avoid elastic recoil and flow-limiting dissections [59].…”
Section: Drug-coated Balloonsmentioning
confidence: 99%
“…However, most recent studies have identified an angiographic reference vessel <3 mm as the most appropriate cut-off. [19] Therefore, it can be stated that any coronary vessel amenable to percutaneous treatment with a 2.75 mm or smaller device should be considered ‘small’. [17] Some authors have suggested the term ‘very small vessel coronary artery disease’ for those coronary vessels that are amenable to percutaneous treatment with a 2 mm device.…”
Section: Definition and Prevalence Of Small Vessel Coronary Artery DImentioning
confidence: 99%
“…DEBs mechanically open obstructed vessels by inflating; this releases a homogeneous high dose of anti-proliferative drug (such as paclitaxel). The resultant reduction in neointimal proliferation prevents restenosis of the obstructed vessel [2,5].…”
Section: Introductionmentioning
confidence: 99%